Analisis usaha perkembangan budidaya ikan dalam jaring apung di Desa Tandengan Kabupaten Minahasa - Pontoh, Otniel (Universitas Sam Ratulangi, 2014)
Abstract The research aimed to study the potential of fish culture in floating net and its development at Tandengan Village Minahasa Regency. This research was a case study and the data collected was analyzed qualitatively with a simple mathematical calculations. Observation and interview to the fishermen who had floating net culture were used to gather the primary and secondary data. The results showed that education degree of fish culturist was 20% elementary school, 20% intermediate school, 60% high school, and 10% bachelor. People experience in running fish culture activity was over 10 years in average. Fish culture activities increased year by year. The problems faced by fish culturist included weather, water condition, food price, and market demand. The increase of floating net culture activities in this area had resulted in the increase of labor demand. The skill of fish culturist needed to be develop through education and training as well as through establishing fish culturists cooperation considering there were many fish culturists present at Tandengan village. This was important due to the development of floating net culture had positive impact in providing working opportunity and increasing people welfare. Keywords : Tandengan Village, case study, fish culture, floating net